The blacklist. The complete sixth season [videorecording (DVD)] - Spader, James; Boone, Megan, 1983-; Klattenhoff, Diego (Sony Pictures Home Entertainment, 2019)
Following the startling revelation that Raymond 'Red' Reddington isn't who he says he is, Elizabeth Keen is torn between the relationship she's developed with the man claiming to be her father and her desire to get to the bottom the secrets and lies. Meanwhile, Red leads Liz and the FBI to the most strange and dangerous criminals yet and eliminating rivals in the process. All throughout, Liz and Red engage in an uneasy cat-and-mouse game in which lines are crossed and the truth will be revealed.